Renal Cell Carcinoma Of The Kidney Presenting As A Renal Abscess: A Rare Case Report - Uddin, Nazim; Md Arif, -; Biswas, Ranen; Zaman, Waheed (Bangladesh Journal of Urology, 2020)
We report a case of renal tumor presented to us as a case of renal abscess extending to subcutaneous space and finally she was diagnosed as a case of renal cell carcinoma with metastatic para-caval lymphadenopathy. Renal cell carcinoma rarely present with renal and perinephric abscess. The association of renal tumor with renal and subcutaneous abscess can lead to misinterpretation on standard imaging procedures and subsequently mislead to select optimum treatment option. Malignancy may be considered as an underlying cause for the formation of a renal abscess, especially if no other predisposing factors such as diabetes or urinary stones are present. Bangladesh Journal of Urology, Vol. 16, No. 1, Jan 2013 p.33-34